2005
DOI: 10.1089/ham.2005.6.209
|View full text |Cite
|
Sign up to set email alerts
|

The Maximum Expiratory Flow-Volume Loop in Natives of Ladakh and Acclimatized Lowlanders

Abstract: Differences in static and dynamic volumes may exist between high altitude residents of Indian Himalayas and their South American counterparts, as well as with acclimatized lowlander sojourners. Maximum expiratory flow-volume loops were recorded in healthy native highlanders of Ladakh (NH, N = 75) and in healthy acclimatized lowlanders (AL, N = 32) at an altitude of 3450 m in the western Indian Himalayas. The forced vital capacity (FVC) and forced expiratory volume in the first second (FEV1), both corrected for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…Tibetans compared to lowlanders have larger chest circumference, larger total lung capacity, and larger vital capacity (Sun et al, 1990;Droma et al, 1991;Apte and Rao, 2005). This difference is already apparent at adolescence (Cheng et al, 1997), corroborating the contention that being born and raised at high altitude leads to increased lung volumes, as reported earlier in Andeans (Brody et al, 1977).…”
Section: Staticssupporting
confidence: 83%
See 1 more Smart Citation
“…Tibetans compared to lowlanders have larger chest circumference, larger total lung capacity, and larger vital capacity (Sun et al, 1990;Droma et al, 1991;Apte and Rao, 2005). This difference is already apparent at adolescence (Cheng et al, 1997), corroborating the contention that being born and raised at high altitude leads to increased lung volumes, as reported earlier in Andeans (Brody et al, 1977).…”
Section: Staticssupporting
confidence: 83%
“…In Ladakhis, maximum expiratory flow-volume loops show greater forced vital capacity (FVC) and forced expiratory volume in the first second (FEV1) compared to acclimatized lowlanders. Flow rates were especially higher at low lung volumes (Apte and Rao, 2005). Altitude-born and -living residents of Tibetan ethnicity thus have greater lung recoil or greater total cross-sectional area of airways (or both) compared to acclimatized lowlanders.…”
Section: Dynamicsmentioning
confidence: 88%
“…Our findings of greater than predicted lung function are similar to thse reported previously for Lahdaki highlanders. 47, 48 Wood et al47 suggested that the augmented lung mechanics of this high-altitude population is adaptive to reduce the work of breathing. Apte and Rao48 further suggested an inherited adaptive mechanism resulting in greater lung elastic recoil and larger cross section of the small airways.…”
Section: Discussionmentioning
confidence: 99%
“…Lung volumes and capacities are known to exhibit strong ethnic differences. [11][12][13] We had the opportunity to study the changes in pulmonary function on acute ascent and during a 4-week stay at an altitude of 3200 m in human male volunteers from 2 different populations: Indians and Kyrgyzis.…”
Section: Introductionmentioning
confidence: 99%